Increased experiences of loneliness during the COVID‐19 pandemic, emotional distress and changes in perceived physical and mental health: A structural equation model - JoAnn Jabbari; Stephen Roll; Amy McQueen; Nancy Ridenour (Wiley, 2024)
Abstract Aim To explore how experiences of increased loneliness during the COVID‐19 pandemic affected emotional distress and changes in perceptions of physical and mental health. Design Cross‐sectional study. Methods Data from the Socio‐Economic Impacts of Covid‐19 Survey, a national survey administered to 5033 adults in August and September 2020 in the United States, was utilized in this study. Structural equation modelling was used to analyse the associations between increased experiences of loneliness during the pandemic, emotional distress and changes in perceptions of physical and mental health. Results Among the 47% of participants who reported increased experiences of loneliness during the pandemic, 31% reported a poorer perceived change in mental health and 12% reported a poorer perceived change in physical health. Increased experiences of loneliness during the pandemic were significantly associated with emotional distress and poorer perceived mental and physical health changes. Emotional distress significantly mediated the effect between increased experiences of loneliness during the pandemic and poorer perceived mental and physical health changes. These findings highlight the importance of producing preventative actions to combat increased loneliness and emotional distress during and after future pandemics in order to improve health perceptions, which can result in negative health outcomes over time.